From 0 to II in One‐Electron Steps: A Series of Ruthenium Complexes Supported by TropPPh2. (25th August 2016) - Yang, Xiuxiu; Gianetti, Thomas L.; Harbort, Joshua; Wörle, Michael D.; Tan, Lilin; Su, Cheng‐Yong; Jurt, Pascal; Harmer, Jeffrey R.; Grützmacher, Hansjörg
Abstract: We report the synthesis of a series of ruthenium complexes supported by the phosphine olefin ligand tropPPh2 (trop=5‐H‐dibenzo‐[a, d]cyclohepten‐5‐yl) in the oxidation states 0, +I, and +II, formed via successive one‐electron oxidization steps from Ru 0 (tropPPh2 )2 . The bidentate character of the tropPPh2 ligand and its steric hindrance force the complexes to adopt uncommon geometries, which were investigated by X‐ray diffraction analysis. EPR data of the mononuclear Ru I complex reveal couplings of the unpaired spin with the ruthenium and two phosphorus nuclei, as well as the olefinic protons which show that the spin is mainly localized on the Ru I center.